Synchronization of the Material Content of Legislation Concerning Connected Corruption Post Constitutional Court Decision Number 87/PUU-XXI/2023 - Bachmid, Fahri (SIGn Journal of Social Science, 2024)
This study examines the implications of Constitutional Court Decision Number 87/PUU-XXI/2023 on the authority of the KPK in handling connected corruption cases. Specifically, this study aims to analyze the material content drafting of the KPK Law post a quo decision, and to formulate recommendations for synchronization with the Criminal Procedure Code and the Military Court Law. This normative legal research uses a statute approach and a case approach, with legal interpretation, legal construction, and legal synchronization analysis techniques. The results show that a quo decision affirms the KPK’s authority to handle connected cases, as long as the case is handled or discovered by the KPK from the outset. The logical-juridical consequence of a quo Decision is the necessity to reconstruct the material content, especially Article 42 of the KPK Law. As formal criminal procedural law, exceptions to the applicability of the connectedness provisions in the Criminal Procedure Code and the Military Court Law also require adjustment. This synchronization is essential to realize legal certainty and the effectiveness of eradicating connected corruption.